Connecting Through Flipgrid : Examining Social Presence of English Language Learners in an Online Course During the Pandemic. (31st December 2022) - Yeh, Ellen; Choi, Grace; Friesem, Yonty
Abstract : This study focuses on the social presence framework (Rourke et al., 2001), in order to examine the ways that university-level international students develop social interaction and support in a virtual asynchronous learning community in an online class during the COVID-19 pandemic. English language learners (ELLs) participated in weekly online exchanges on a video discussion platform called Flipgrid in the form of oral dialogue journals for reflection on their academic learning and experiences during these disruptive times. These ELLs' video journals and peer responses (N = 198) were collected for content analysis, in order to investigate how the use of video-based asynchronous computer-mediated communication (ACMC) can establish positive social and emotional support and a sense of community. The findings of the study indicate that ACMC was successful in establishing interconnectedness in terms of high levels of selfdisclosure, positive facial expressions, and other indicators of social and emotional support, demonstrating social presence. Implications of the findings are discussed in terms of how social presence is expressed and fostered in videobased ACMC communities during emergency remote teaching.